Physical Therapy Education on Preventing Speech Delays by Limiting Screen Time at the Wonokoyo Neighborhood Health Post, Malang City : Penyuluhan Fisioterapi mengenai Pencegahan Speechdelay dengan Mengontrol Screen Time di Posyandu Kelurahan Wonokoyo, Kota Malang - Felix Nashar Novanto; Sri Sunaringsih Ika Wardojo; Ratih Wijastuti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The increasing use of electronic devices among young children often results in screen time that exceeds recommended limits, potentially disrupting language development and increasing the risk of speech delay. This is a cause for concern because speech delay can impact a child’s future communication skills, social interactions, and cognitive development. Based on observations at the RW 5 Posyandu in Wonokoyo Village, Malang City, there are still parents who allow their children to use electronic devices for extended periods without adequate supervision. The purpose of this exercise is to raise parents' awareness and understanding about minimizing speech delays by limiting screen time. Physiotherapists employ health education as a tool, providing parents of toddlers with information, interactive conversations, questions and answers, and instructional media in the form of posters. Pre-test and post-test approaches were used in the evaluation process to gauge the participants' comprehension. According to the activity's results, participants' knowledge of speech delay increased from 30% to 95%, and their comprehension of the reasons why screen time causes speech delay increased from 10% to 80%, an increase in knowledge of ideal screen time limits from 0% to 95%, and an increase in understanding of how to manage screen time from 10% to 90%. The impact of the activity was reflected in increased parental awareness regarding limiting device use and providing more optimal communication stimulation to children as a preventive measure against speech delay.